Projeto de um modelador 3D colaborativo baseado no padrão emergente MPEG-4 MU - Duarte, Fernando Vieira (2003)
In the last years we have been experiencing advances in networking technologies as well as computer graphics and display technology. As a consequence, a lot of Collaborative Virtual Environments have emerged thanks to the increasing computation capabilities of desktop computers as well as the enormous growth in network bandwidth and the ubiquity of the Internet. Collaborative virtual environments for 3D modeling can be characterized by the interaction among multiple users for the creation and/or modification of shared 3D objects. These environments can be used, for instance, in the modeling and visualization of virtual prototypes in order to reduce costs in the process of products design. The challenges of building collaborative 3D modeling environments are mainly related to real-time rendering of the modified objects, as well as to users interaction with the virtual environment, and to consistency maintenance of the shared virtual environment. Only a few collaborative 3D modeling environments are found in the literature and usually their projects result in complex non standardized solutions for the collaboration among users. This work presents the implementation of a collaborative environment for 3D modeling based on the emerging MPEG-4MU (multi-user) standard. With this environment, 3D graphic scenes can be created in real-time, by multiple participants, in synchronous collaborative sessions. These scenes can be visualized in any MPEG-4 terminal, including cellulars and personal digital assistants (PDAs). Sessions control, consistency maintenance, concurrency control and 3D object locking are realized by the MSC (MUTech Session Controller) and MBK (MUTech Bookkeeper) components, through the Pilot/drone mechanism and the BIFS-Command protocol. All these components were defined by the MPEG-4 MU emerging standard and implemented by the Networked Virtual Reality Lab (LRVNet) at Federal University of São Carlos.